EDUKASI CEMARAN MIKROBA PADA OBAT, KOSMETIK, MAKANAN, DAN LINGKUNGAN BAGI SISWA/I DI SMK SWASTA TIK DARUSSALAM - Candrika; Desni Rinanda Silitonga; Betharina Br Tarigan; Angel Ronauli Siahaan; Dela Cintya; Gladies Trya Sintikhe Mendrofa; Hamdan Pajaya; Iche Oktaviany Br Damanik; Julpinter Harefa; Melisabila Utami; Naila Pardede; Tresya Siregar; Yolanda Silaban (CV. Lafadz Jaya, 2026)
Microbial contamination is a health issue that requires serious attention from various parties. The presence of harmful microbes in cosmetic products, medicines, food, and the surrounding environment can pose health risks that cannot be ignored, ranging from mild infections to life-threatening chronic diseases. Therefore, educating students about this is very important and urgent to be implemented. This study aims to provide education to increase students' knowledge and awareness regarding microbial contamination in medicines, cosmetics, food, and the environment through health education activities for students at SMK SWASTA TIK DARUSSALAM. The method used was health counseling with material presentations, distribution of educational brochures about microorganisms, accompanied by ice-breaking activities to increase student participation. The material provided included types of microbes, risks of contamination, dangers of microorganisms, and efforts to implement a healthy and clean lifestyle. The results of the activity showed an increase in students' understanding of the importance of washing hands with soap, maintaining environmental cleanliness, and awareness of the importance of implementing clean and healthy lifestyle behaviors. In addition, students showed enthusiasm and active participation during the activity. With ongoing health education and support from the school, it is hoped that students will be able to implement preventive behavior independently and become agents of change in creating a school environment that is healthy, safe, and free from disease transmission.